2015
DOI: 10.1024/1012-5302/a000446
|View full text |Cite
|
Sign up to set email alerts
|

Erfahrungen und Bedürfnisse von Eltern hospitalisierter Kinder mit Behinderung und den in der Betreuung verantwortlichen medizinischen Fachpersonen – Eine systematische Review

Abstract: Considering the burden experienced by parents, their support must be of central concern for all health professionals. Nurses can support parents and thus the hospitalized child in the adjustment process by focused preparation and continuous attendance based on family-centred care. The latter must be supported by the management and the multidisciplinary team to tailor the competences and the organization accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Nessa perspectiva, intervenções de enfermagem devem ser direcionadas às reais demandas das famílias, visando tornar a doença e a hospitalização da criança uma experiência menos traumática e fatigante 10,25 , prevenindo e revertendo desequilíbrios, por meio de uma assistência ao ser humano direcionada ao atendimento de suas necessidades básicas 16 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Nessa perspectiva, intervenções de enfermagem devem ser direcionadas às reais demandas das famílias, visando tornar a doença e a hospitalização da criança uma experiência menos traumática e fatigante 10,25 , prevenindo e revertendo desequilíbrios, por meio de uma assistência ao ser humano direcionada ao atendimento de suas necessidades básicas 16 .…”
Section: Discussionunclassified
“…Além disso, conhecer as demandas de cuidado permite, à equipe de saúde, implementar intervenções que qualificam e humanizam a assistência às famílias, ajudando-as a superar fontes de angústia e estresse, e possibilitando a transformação da prática profissional de modo a evitar a fragmentação do cuidado 4,10 .…”
Section: Introductionunclassified
“…In order to systematically explore the parents' specific experiences and support needs, we began by conducting a systematic review (Seliner et al, 2015) followed by a qualitative and a cross-sequential study involving parents of hospitalized children with PIMDs at the children's hospital in question (Seliner et al, 2016a(Seliner et al, , 2016b. Both studies showed a need for quality improvement at all levels.…”
Section: Theoretical Base Of the Intervention Development (Phase 1)mentioning
confidence: 99%